Managing fetuses at high risk of retinoblastoma: lesion detection on screening MRI. (27th November 2014) - Staffieri, Sandra E.; McGillivray, George; Elder, James E.; Bristowe, Amber; Cole, Stephen; McKenzie, John D.; Fink, A. Michelle
Abstract Objective This study aimed to describe tumour identification on magnetic resonance imaging (MRI) in a 35‐week fetus with familial retinoblastoma (RB) and report the use of prenatal ultrasound (US) and MRI screening in the management of fetuses at high risk of RB. Method This is a retrospective review of the prenatal course and immediate postnatal findings in all children considered at high risk of RB who had prenatal imaging with both US and MRI at our institution over a 5‐year period. Results Five patients met the inclusion criteria. No lesions were identified on US in any patients. Fetal MRI identified bilateral posterior pole lesions in one patient at 35 weeks' gestation. Of the four remaining patients, three developed lesions by 5 weeks of age. Only one fetus was delivered early following detection of RB. Conclusion We present the first reported case of RB detected in a high‐risk fetus on screening MRI at 35 weeks' gestation. A protocol for screening this population using both imaging modalities is presented. © 2014 John Wiley & Sons, Ltd.